Community-Based English Corner Sebagai Model Transformasi Layanan Kedai Desa Wisata Kahayya - Rostina Rostina; Muhaidir Ikram M; Josafat Gracia Ginting (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aimed to transform tourism kiosk services through the development of a Community-Based English Corner as a community empowerment initiative to improve tourism service quality. The program was implemented over three months using a participatory approach consisting of five stages: socialization, intensive training, technology and innovation implem entation, mentoring and evaluation, and program sustainability. The activities included English for Tourism training, the development of English-language digital promotional content, and the provision of bilingual information media for three tourism kiosks. The results demonstrated the establishment of an English Corner learning community, improved participants’ English communication skills and digital promotion competencies, the availability of bilingual information media, and the production of promotional content supporting destination marketing. Overall, the program enhanced community-based tourism services, strengthened the competitiveness of local businesses, encouraged community participation, supported the achievement of the Sustainable Development Goals (SDGs), and can serve as a replicable community empowerment model for other tourism destinations.